Development Strategy for Salt Business in Rembang Regency - Putri Arie Rachma; Husna Faizah Khotimatul; Nurrokhmini Alfiati; Basuki Basuki; Al Hakim Humairoh; Purwanti Asih (E3S Web of Conferences)
Indonesia is a country with great potential in salt production. The high salt imports suggest that the potential has yet to reach its full potential. Salt produced by the coastal communities of Rembang Regency has the potential for further development. The research objective is to identify the development strategy for the salt business in Rembang Regency by analyzing internal and external factors through SWOT analysis. The research results show that internal factors of the salt business include supporting and inhibiting factors. The lack of electronic media usage and promotion are inhibiting factors, while education level, age, and experience are supporting factors from the internal perspective. External inhibiting factors for the salt business include business competition. External supporting factors include the availability of raw materials, enabling increased production. With both supporting and inhibiting factors from internal and external perspectives, the development strategy for the salt business in Rembang Regency involves enhancing digital and online promotion and marketing skills and improving product quality to enhance competitiveness.